2015
DOI: 10.1007/s00127-015-1038-x
|View full text |Cite
|
Sign up to set email alerts
|

The gender gap in mental health service use

Abstract: The gender gap in mental health service use is due not only to men and their negative attitudes toward help seeking, but also to structured social norms that are reconstructed in interactions. Women also contribute to the maintenance of masculinity norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 36 publications
11
64
2
1
Order By: Relevance
“…This is in line with the literature that converged upon the same conclusion (Gallegos et al, 2015;O'Loughlin et al, 2011;Pattyn et al, 2015;Yousaf et al, 2015). This is in line with the literature that converged upon the same conclusion (Gallegos et al, 2015;O'Loughlin et al, 2011;Pattyn et al, 2015;Yousaf et al, 2015).…”
Section: Male-female Differences In Baseline Help-seekingsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with the literature that converged upon the same conclusion (Gallegos et al, 2015;O'Loughlin et al, 2011;Pattyn et al, 2015;Yousaf et al, 2015). This is in line with the literature that converged upon the same conclusion (Gallegos et al, 2015;O'Loughlin et al, 2011;Pattyn et al, 2015;Yousaf et al, 2015).…”
Section: Male-female Differences In Baseline Help-seekingsupporting
confidence: 91%
“…When only considering measurements at baseline (i.e., before consideration of preferences for or availability of a therapist of the preferred sex), the current study found lower help-seeking of males than females, in agreement with the consensus in the literature (Gallegos et al, 2015;O'Loughlin et al, 2011;Pattyn et al, 2015;Yousaf et al, 2015). However, for sex of respondent, the following interesting findings were observed.…”
Section: Accommodating Preferences For Therapists' Sex Predicts Helsupporting
confidence: 90%
“…Despite these methodological differences, our low rate probably reflects a low access to psychiatric specialist care in Tromsø, Norway, as reported elsewhere [28]. In addition, the low rate might be related to stigma, leading people not to seek care in specialist psychiatric settings [29, 30]. Another possible explanation is that some people with anxiety/depression might be satisfied with care from one provider, whether care is offered by a CAM provider or a mental care specialist.…”
Section: Discussionmentioning
confidence: 61%
“…We excluded representative samples that were limited to one large city or region or even several regions (if they were not randomly selected). We also excluded samples of inpatients or outpatients as this sampling strategy is vulnerable to the criticism that the study is detecting a gender difference in help seeking rather than an actual gender difference in depression (Nolen-Hoeksema, 1987; Pattyn, Verhaeghe, & Bracke, 2015). Nationally representative samples do include individuals currently receiving mental health treatment (unless they are institutionalized) or individuals with a history of receiving mental health treatment, so those individuals were not excluded.…”
Section: Methodsmentioning
confidence: 99%